TEI Pedagogy and TAPAS Classroom - Julia Flanders (OpenEdition, 2019)
This paper focuses on recent work by the TEI Archiving, Preservation, and Access Service (TAPAS) on pedagogy with TEI, and specifically on a recent initiative called “TAPAS Classroom” focused on exploring pedagogical uses of TEI. We provide some background on TAPAS, describe several case studies involving pedagogical partners who used TAPAS in teaching, and finally describe the TAPAS Classroom initiative and its outcomes.